2016
DOI: 10.1111/hel.12298
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Activates IL‐6‐STAT3 Signaling in Human Gastric Cancer Cells: Potential Roles for Reactive Oxygen Species

Abstract: H. pylori-induced STAT3 activation is mediated, at least in part, through ROS-induced upregulation of IL-6 expression. These findings provide a novel molecular mechanism responsible for H. pylori-induced gastritis and gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Upregulated expression of IL-6 has been noted previously in O. viverrini (16) and H. pylori single infections (17), which might synergistically induce inflammation-mediated liver injury through oxidative stress (12,17). As a result of this, the lipopolysaccharide of bacteria, including H. pylori, can induce TGF-␤ signaling through Toll-like receptor 4 (18), contributing to fibrogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…Upregulated expression of IL-6 has been noted previously in O. viverrini (16) and H. pylori single infections (17), which might synergistically induce inflammation-mediated liver injury through oxidative stress (12,17). As a result of this, the lipopolysaccharide of bacteria, including H. pylori, can induce TGF-␤ signaling through Toll-like receptor 4 (18), contributing to fibrogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…demonstrated that the oxidative burst induced by H. pylori in human gastric epithelial cells is responsible for the PI3K/AKT1-dependent expression of the transcription factor Snail family zinc finger 1 (SNAI1, also known as SNAIL) [111], which is essential for epithelial-mesenchymal transition and therefore in gastric cancer progression and metastasis. Additionally, it has been shown that the transcription factor signal transducer and activator of transcription 3 (STAT3), which plays a major function in inflammation and angiogenesis, is also induced in gastric epithelial cells via upregulated autocrine IL-6 signaling, partially mediated by endogenous ROS [112]. Moreover, α-lipoic acid, a naturally occurring thiol compound that exhibits antioxidant properties, inhibits NOX-derived ROS production in AGS cells and concomitantly dampens NF-κB and AP-1 activation and expression of the oncogenes β-catenin (CTNNB1) and MYC [113].…”
Section: Endogenous Effect Of Ros On the Hostmentioning
confidence: 99%
“…(2016) have demonstrated that the oxidative burst induced by H. pylori in human gastric epithelial cells is responsible for the phosphoinositide 3-kinase (PI3K)/AKT serine/threonine kinase 1 (AKT1)/glycogen synthase kinase 3 beta (GSK3B)-dependent expression of the transcription factor Snail (SNAI1) (Ngo et al 2016), which is essential for epithelial-mesenchymal transition and therefore in gastric cancer progression and metastasis. Additionally, it has been shown that the transcription factor signal transducer and activator of transcription 3 (STAT3), which plays a major function in inflammation and angiogenesis, is also induced in gastric epithelial cells via upregulated autocrine IL-6 signaling, partially mediated by endogenous ROS (Piao et al 2016). Lastly, α-lipoic acid, a naturally occurring thiol compound that exhibits antioxidant properties, inhibits NADPH oxidase-derived ROS production in AGS cells and concomitantly dampens NF-κB and AP-1 activation and expression of the oncogenes β-catenin (CTNNB1) and c-Myc (MYC) (Byun et al 2014).…”
Section: Induction and Role Of Rosmentioning
confidence: 99%